2020
DOI: 10.1051/e3sconf/202017201003
|View full text |Cite
|
Sign up to set email alerts
|

Internal insulation of solid masonry walls – field experiment with Phenolic foam and lime-cork based insulating plaster

Abstract: The study investigated the hygrothermal performance and risk of mould growth in two thermal insulation systems for internal retrofitting purposes; a phenolic foam system with a closed cell structure, and a capillary active diffusion-open lime-cork based insulating plaster. The setup consisted of a 40-feet (12.2 m) insulated reefer container with controlled indoor climate, reconfigured with several holes (1x2 m each) containing solid masonry walls with embedded wooden elements on the interior side and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The tendencies observed for the PUR-CM and AAC systems were in agreement with the experimental findings in [42]. The observations for the Phenolic foam system in the interface were however contradictory to the experimental findings [43], as progressively decreasing RH levels were found in the field study while the modelling results predicted increased RH levels. The discrepancies could perhaps be related to the problem with incorrect installation of the Phenolic foam system in the field study mentioned in Section 4.1.…”
Section: Future Climate Predictionssupporting
confidence: 80%
See 3 more Smart Citations
“…The tendencies observed for the PUR-CM and AAC systems were in agreement with the experimental findings in [42]. The observations for the Phenolic foam system in the interface were however contradictory to the experimental findings [43], as progressively decreasing RH levels were found in the field study while the modelling results predicted increased RH levels. The discrepancies could perhaps be related to the problem with incorrect installation of the Phenolic foam system in the field study mentioned in Section 4.1.…”
Section: Future Climate Predictionssupporting
confidence: 80%
“…Regarding the reliability of mathematical mould growth models, previous studies [49], [67]- [71] indicate that the mathematical models are not able to precisely predict the extent of the mould growth infestation, but should instead be used to predict the likelihood of mould growth occurring in the structure or as a comparative tool to evaluate different design solutions. The experimental findings from the field study [42], [43] showed large discrepancies between on-site tests and model predictions. The application of the mould-growth model in this study was therefore used to assess the observed tendencies which include temperature, RH and time into the risk evaluation.…”
Section: Risk Of Mould Growthmentioning
confidence: 92%
See 2 more Smart Citations
“…Older masonry may benefit from external rain protection like hydrophobization since it can prevent or at least obstruct the penetration of precipitation by effectively blocking the capillary suction without effecting the vapor diffusion of the wall, as shown in [8] and [17]. However, experimental results on the combination of hydrophobization with internal insulation in solid masonry walls also show in certain studies [25,26] that the effect of hydrophobization not always is positive. Both diffusion open and tight insulation systems are subject to this problem.…”
Section: Moisture Sources and Protectionmentioning
confidence: 99%